The elements of financial performance contribute financial distress among service companies in Malaysia / Saifatul Hazirah Saidin - Saidin, Saifatul Hazirah (2011)
The purpose of this study is to predict the business failure of the selected companies which are listed under services sector. The paper‟s aim to test the usefulness of ratio analysis to predict the financial distress / bankruptcy of the companies in a period of Malaysia faced the crisis economy in 2009. The paper examines the correlation of traditional financial ratios with sector performance for a large sample of Malaysia companies under services sector. A propriety Z-score failure prediction model is used to evaluate the solvency of 100 companies. The paper identifies that certain companies will be faced the financial distress matter by looking the financial statement of 2009. Data availability constitutes the primary limitation of this and similar studies, here is reflected in the sample size: 45 safe zones, 23 grey zone and 32 in the distress zone. The model can be used to assist investors, creditors, and regulators in Malaysia to predict the business failure. The Z-score model of Altman can be used for public companies because it pays attention to solvency indicators, but rapid changing environment, profitability ratios should also considered. This article is of use in identifying what information is useful in annual reports.